2017
DOI: 10.1111/jcpp.12683
|View full text |Cite
|
Sign up to set email alerts
|

Oppositional defiant disorder dimensions: genetic influences and risk for later psychopathology

Abstract: Background This study was undertaken to determine how well two Oppositional Defiant Disorder (ODD) dimensions (irritable and headstrong/hurtful) assessed in childhood predict late adolescent psychopathology and the degree to which these outcomes can be attributed to genetic influences shared with ODD dimensions. Methods Psychopathology was assessed via diagnostic interviews of 1225 twin pairs at ages 11 and 17. Results Consistent with hypotheses, the irritable dimension uniquely predicted overall internali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Several studies demonstrate moderate genetic influences on irritability, with heritability estimates ranging from 31% to 54% across studies in the UK 17 , Sweden 18,19 and USA 20 . Moderate heritability estimates for defiant behavior, ranging from 41% to 45%, also have been reported in these studies, with moderate shared environmental influences as well.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrate moderate genetic influences on irritability, with heritability estimates ranging from 31% to 54% across studies in the UK 17 , Sweden 18,19 and USA 20 . Moderate heritability estimates for defiant behavior, ranging from 41% to 45%, also have been reported in these studies, with moderate shared environmental influences as well.…”
Section: Introductionmentioning
confidence: 99%
“… 18 This study derived a two-factor solution of ODD symptoms, namely, irritability and “headstrong” symptoms, and showed that irritability symptoms predicted anxiety disorders more strongly than headstrong symptoms (arguing with adults, defying adults’ requests). Another recent study conducted in twin pairs (n=1,225) by Mikolajewski et al 21 found consistent evidence of an “irritable” dimension predicting internalizing problems and a headstrong/hurtful dimension of substance-use disorder symptoms. Additionally, shared genetic risk between the dimension and the disorders was demonstrated.…”
Section: Nosology Of Oddmentioning
confidence: 86%
“…Shared environment was the weakest contributor. 21 A recent meta-analysis showed around 50% variance of CD comes from additive genetic effects. In this study, along with unshared environmental components, there was a significant shared environmental component, eg, parenting practices or neighborhood.…”
Section: Etiopathological Influencesmentioning
confidence: 99%
“…According to the DSM-5 criteria, the diagnosis oppositional defiant disorder requires the presence of a specific pattern of a behavior which includes at least four out of 8 symptoms from any of the bellow listing categories that the child exhibits when interacting with at least one subject who is not a sibling (APA, 2013: 462): Recent research has shown that the oppositional defiant disorder might have two separate symptom dimensions: affective and behavioral. Based on these two phenomenologicallydistinct signs of the disorder, two types of oppositional defiant disorder have been distinguished: the one subtype is characterized by affective symptoms of irritability, temper tantrums, and resentful attitude, and the other subtype is characterized with the features of defiance like vindictiveness and arguing (Mikolajewski, Taylor & Iacono, 2017).…”
Section: Oppositional Defiant Disordermentioning
confidence: 99%